Pengaruh Gaya Kepemimpinan terhadap Kinerja Dosen dengan Kepuasan Kerja dan Motivasi Kerja sebagai Mediator (Studi pada Perguruan Tinggi Swasta di Jayapura) - Taruno, Soewarto Citro; Thoyib, Armanu; Zain, Djumilah; Rahayu, Mintarti (Universitas Brawijaya, Indonesia, 2012)
The research objective is to reveal and investigate the direct and indirect influence of leadership style on the work performance of private university lecturers in Jayapura. Quantitative approach was applied to achieve the research objective. The data are analyzed by applying a statistic technique PLS (Partial Least Square). The research findings are: (1) the biggest contribution of the influence of leadership style towards the lecturers'work performance in series are: (a) work motivation line as a mediator, (b) work satisfaction line as a mediator, (c) combination of work satisfaction and work motivation line as a mediator. (2) to create better lecturers'work performance, a leader should: (a) be more creative and initiative, help in problems solving, enhance the lecturers, and follow the surrounding movements, (b) be able to create comfortable feeling for the lecturers so that they have great interest to their jobs, and create joyful work environment, and (c) be able to improve lecturers'work motivation through the togetherness in work, pay attention to carrier promotion, and give achievement to the lecturers having good work performance.